Implementasi Metode Clustering Partitional Menentukan Item Slow Moving dan Fast Moving Pada Persediaan Barang (Studi Kasus PT. SAT) - Herdianto Siahaan (JURIKOM (Jurnal Riset Komputer), 2019)
This Clustering method is used to group items in two types, namely fast moving and slow moving. By grouping goods into these two groups, the handling of goods according to their types will create efficient goods turnover. This research was compiled to provide an overview of how a computerized clustering method determines the category of slow moving and fast moving in the inventory at the SAT NGUMBAN SURBAKTI store produced. Data collection is done by going directly to the field and consulting with employees and supervisors, there is a programming language used to solve existing problems using Visual Basic 2008 language and MySQL database. From the discussion, the author can draw the conclusion that computers will be very helpful in solving problems faced and support the creation of work processes that are very fast, precise and accurate.